Hubungan Tingkat Stres Akademik dengan Perilaku Makan pada Mahasiswa Sarjana Fakultas Kesehatan Masyarakat Universitas Airlangga - Salma Aulia Rizqi Nuramalia; Sri Sumarmi (Universitas Airlangga, 2024)
Background: College students are a group of individuals who belong to adolescence and young adulthood with generally poor eating habits that can be caused by various factors. Pressure in academic matters is one of the main factors of student stress, such as the desire to get high grades and student anxiety to try not to fail. Students often neglect some routines that can actually support performance in learning, one of which is eating. This kind of lifestyle is associated with poor health, which in turn affects life satisfaction. Life satisfaction of young adults is related to eating, because eating can determine health conditions. Objective: This study aims to analyze the relationship between academic stress levels and eating behavior in undergraduate students of the Faculty of Public Health, Universitas Airlangga. Methods: This study was a quantitative study with a cross sectional approach. The research samples was 60 people, obtained randomly by simple random sampling on Microsoft Excel. Data collection included filling out a questionnaire of respondent characteristics, academic stress levels with the Student-Life Stress Inventory, and eating behavior with the Adult Eating Behaviour Questionnaire. Data analysis used in this study was Spearman correlation test. Results: It was found that 58.3% of students had eating behavior that tended to food avoidance and 41.7% of students have eating behavior that tended to food approach. A total of 58.3% of students experienced academic stress levels. There was a relationship between academic stress level (p = 0.001) and eating behavior. Conclusion: The conclusion of this study is that students who have moderate levels of academic stress experience eating behaviors that tend to be food avoidance. It is recommended that students still be able to manage stress well and regulate eating behavior by choosing foods that are in accordance with the principles of balanced nutrition and not skipping breakfast or eating.